Hydroxytyrosol mildly improve cognitive function independent of APP processing in APP/PS1 mice. Issue 11 (25th July 2016) - Peng, Yunhua; Hou, Chen; Yang, Ziqi; Li, Caixia; Jia, Liyan; Liu, Jing; Tang, Ying; Shi, Le; Li, Yongqin; Long, Jiangang; Liu, Jiankang
Abstract : Hydroxytyrosol (HT) can be transported across the blood–brain‐barrier and exert roles in neurons. HT improves electroencephalography activity and marginally benefits cognitive behavior of Alzheimer's disease (AD) mice. These results suggest that HT may represent as a functional ingredient in the Mediterranean diet in ameliorating AD‐involved neuronal impairment via modulating mitochondrial oxidative stress, inflammation, and apoptosis without affecting AβPP processing. Abstract : Scope: Olive products, the hallmark of Mediterranean diet, are associated with reduced risk of mild cognitive impairment and Alzheimer's disease (AD). We and other groups have shown that hydroxytyrosol (HT), a bioactive compound of olive products, ameliorates oxidative stress, mitochondrial dysfunction, and neural toxicity. However, whether HT in Mediterranean diet acts as a functional ingredient in delaying AD pathogenesis remains unclear. Methods and results: In the present study, APP/PS1 mice, an animal model of AD, were administrated for 6 months with 5 mg/kg/day of HT, a comparable level of HT in daily Mediterranean diet. HT improved electroencephalography activity and marginally benefited cognitive behavior of transgenic mice. In addition, HT treatment ameliorated mitochondrial dysfunction, reduced mitochondrial carbonyl protein, enhanced superoxide dismutase 2 expression, reversed the phase 2 enzyme system and reduced the levels of brain inflammatory markers, but had no effect on brain β‐amyloid (Aβ) accumulation in APP/PS1 mice. Conclusions: These results suggest that HT may represent as a functional ingredient in Mediterranean diet in ameliorating AD‐involved neuronal impairment via modulating mitochondrial oxidative stress, neuronal inflammation, and apoptosis without affecting APP processing.